New approaches for non-classically damped system eigenanalysis. - Khanlari, Karen (Earthquake engineering & structural dynamics.)
This paper presents three new approaches for solving eigenvalue problems of non-classically damped linear dynamics systems with fewer calculations than the conventional state vector approach. In the latter